1997
DOI: 10.1126/science.278.5337.463
|View full text |Cite
|
Sign up to set email alerts
|

Forward and Backward Propagation of Dendritic Impulses and Their Synaptic Control in Mitral Cells

Abstract: The site of impulse initiation is crucial for the integrative actions of mammalian central neurons, but this question is currently controversial. Some recent studies support classical evidence that the impulse always arises in the soma-axon hillock region, with back-propagation through excitable dendrites, whereas others indicate that the dendrites are sufficiently excitable to initiate impulses that propagate forward along the dendrite to the soma-axon hillock. This issue has been addressed in the olfactory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
166
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(179 citation statements)
references
References 31 publications
9
166
2
2
Order By: Relevance
“…An exception to this rule is the mitral cell of the olfactory bulb. Dendritic patch and voltage-sensitive dye measurements showed that full-size sodium action potentials are regularly triggered in the apical tuft of the mitral primary dendrites (Chen, Midtgaard & Shepherd, 1997;Djurisic et al, 2004). In the present study the peak amplitude of the fast spikelet in the remote dendritic region was always smaller than the amplitude of the backpropagating AP (Fig.…”
Section: The Incidence Of Basal Spikeletsmentioning
confidence: 66%
“…An exception to this rule is the mitral cell of the olfactory bulb. Dendritic patch and voltage-sensitive dye measurements showed that full-size sodium action potentials are regularly triggered in the apical tuft of the mitral primary dendrites (Chen, Midtgaard & Shepherd, 1997;Djurisic et al, 2004). In the present study the peak amplitude of the fast spikelet in the remote dendritic region was always smaller than the amplitude of the backpropagating AP (Fig.…”
Section: The Incidence Of Basal Spikeletsmentioning
confidence: 66%
“…As has been observed in dendritic patch-clamp recordings (Bischofberger and Jonas, 1997;Chen et al, 1997;Margrie et al, 2001;Ma and Lowe, 2004) and calcium-imaging experiments Margrie et al, 2001;Ma and Lowe, 2004) from primary dendrites of other mitral cells, single backpropagating APs cause uniform calcium elevations from soma to tuft in AOB mitral cell primary dendrites. Isolated dendritic spikes have been observed in tufts of main olfactory bulb mitral cells, but only when somatic spikes were prevented by somatic hyperpolarization, either via direct current injection or activation of inhibitory inputs (Chen et al, 1997;Shen et al, 1999). Here, we observed that after synaptic stimulation, tufts of many AOB mitral cells readily fire isolated tuft spikes without initiating somatic APs.…”
Section: Comparison To Other Dendritesmentioning
confidence: 84%
“…Although APs in the apical dendrite of mitral cells propagate reliably and fully for the length of the dendrite (22,23), APs in the lateral dendrites do not. This difference in AP propagation in different dendrites of the same neuron may be unique to mitral cells and may reflect the distinct and specialized functions of apical vs. lateral dendrites.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the propagation of APs in mitral cell lateral dendrites could determine the spatial extent of lateral inhibition evoked by M͞T cell firing. In the apical dendrites of mitral cells, APs back-propagate without decrement (22,23). Here we examine AP propagation in lateral dendrites of mitral cells to determine the conditions under which widespread lateral and recurrent inhibition is activated.…”
mentioning
confidence: 99%